1996
DOI: 10.1021/jp9525245
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Mo−Mg Binary Oxides in Oxidized/Reduced States Studied by X-ray Absorption Spectroscopy at the Mo K Edge and Mg K Edge

Abstract: The local structure around Mo atoms in Mo-Mg binary oxides has been investigated by X-ray absorption spectroscopy at Mo and Mg K edges. XANES and EXAFS spectra show that the binary oxides have a tetrahedral MoO 4 unit in the samples with a Mo/(Mo + Mg) ratio of less than 0.5 and an octahedral MoO 6 unit in the samples with a higher ratio. By H 2 treatment at 773 K, a molybdena-rich binary oxide was easily reduced to form the MoO 2 phase, which was not detected by XRD but was by EXAFS. It is concluded that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 30 publications
(49 reference statements)
3
40
0
Order By: Relevance
“…Furthermore, Aritani et al [25], who obtained the same values, showed that the reduction of molybdenum from +VI to +IV, causes a shrinking of the energy levels. However, as it also implies a lowering of the edge, the difference between a reduction and a modification of symmetry can be made.…”
Section: Reference Compoundsmentioning
confidence: 76%
See 2 more Smart Citations
“…Furthermore, Aritani et al [25], who obtained the same values, showed that the reduction of molybdenum from +VI to +IV, causes a shrinking of the energy levels. However, as it also implies a lowering of the edge, the difference between a reduction and a modification of symmetry can be made.…”
Section: Reference Compoundsmentioning
confidence: 76%
“…Thus, if such a uranium molybdate appears, two components in the white line are expected. The first should be located at 2526.0 eV and the second at an energy gap of about 3 eV as described by Aritani et al [25]. Consequently, it appears impossible to differentiate the formation of a Whatever the hypothesis considered, the result obtained for the sample as implanted clearly shows that the peak located at 2523.8 eV corresponds to a presence of Mo atoms in the matrix grains.…”
Section: Surface: Total Electron Yield Measurementsmentioning
confidence: 82%
See 1 more Smart Citation
“…The Mg K-edge spectra shifted towards higher energy by ~2.2 and ~2.9 eV for Ni 0. 33 Mg 0.67 and Ni 0. 13 Mg 0.87 , respectively, when hydrogen is introduced.…”
Section: Resultsmentioning
confidence: 97%
“…[65][66][67][68][69][70][71][72][73] However, the energy at the 1/2-height of the edge is better, and indicates something close to Mo(VI), since Mo(IV) ½-height energies are typically below 20011 eV when using our chosen energy calibration. 63,64 With such uncertainty, it is not really possible to determine how much Mo(V) is mixed in; we therefore report here that the Mo K-edge XANES are consistent with a Mo(V,VI) state.…”
Section: Resultsmentioning
confidence: 99%